Towards sustainable living in high radiation cold climates: A two-phase genetic algorithm approach for residential building optimization - Mo, Wensheng; Yao, Xingbo; Liu, Zu-An; Chen, Shuo; Li, Qianyu; Jiang, Jiahao; Zhang, Gaochuan; Dewancker, Bart Julien (Building and environment, 2024)
The High Radiation Cold (HRC) region's unique climatic conditions, characterized by high solar radiation and low air temperatures, present distinct challenges for optimizing building climate responsiveness. In this study, residential building design is bifurcated into two phases: building geometry (Phase I) and envelope design (Phase II). In Phase II, we propose a heterogeneous vertical envelope (HVE) design to suit HRC climates. This research framework establishes multiple objectives: energy efficiency, indoor comfort, and economy. It aims to identify a balanced and sustainable design by optimizing various parameters and materials using a Multi-Objective Genetic Algorithms（MOGA). The results indicate enhanced building adaptability in HAV climates through MOGA. The optimal solution in phase I results in an annual heating load of 59.12 W/m2, 33.38 % annual indoor visual comfort hours and the adaptive model predicts 35.59 % annual comfort hours. Incorporating phase II optimization, the total annual energy demand is reduced by 34.42 % with an 11.35 % improvement in thermal comfort hours, culminating at 37.8 %. •Propose a Two-phase method to optimize building climate adaptive design in plateau.•A novel multi-objective optimization of building envelop approach is proposed.•Based on HVE optimization, optimal design parameters were defined for various facade.•Optimization of plateau residential geometry achieves 10–18 % energy savings.•Phase II saved energy by 34.42 %; thermal comfort up by 11.35 %, peaking at 37.8 %.